Hubungan antara Frekuensi Latihan Calf Raise dengan Peningkatan Kekuatan Otot Gastrocnemius pada Mahasiswa Keperawatan Anestesiologi Universitas ‘Aisyiyah Yogyakarta - Roisatin Qonitan; Astika Nur Rohmah; Ratih Kusuma Dewi (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Students, being academically active, may experience reduced physical activity, risking lower extremity strength, particularly in the gastrocnemius muscle. Calf raise exercises can improve this muscle's power. This study aimed to examine the relationship between calf raise frequency and gastrocnemius strength in anesthesia nursing students at Universitas 'Aisyiyah Yogyakarta. Using a pre-experimental one-group pretest-posttest design, 41 students were assessed via total sampling. Muscle strength was measured using a leg dynamometer and observation sheet. Wilcoxon and Spearman Rank tests revealed significant improvement (p = 0.000) and a strong relationship between exercise frequency and muscle strength. Most participants (76.2%) reported high exercise frequency and moderate strength improvement. The findings confirm a significant relationship between calf raise frequency and gastrocnemius strength, suggesting the need for increased student awareness of muscle training.